2009
DOI: 10.1002/cm.20377
|View full text |Cite
|
Sign up to set email alerts
|

β3‐Tubulin is induced by estradiol in human breast carcinoma cells through an estrogen‐receptor dependent pathway

Abstract: Microtubules are involved in a variety of essential cell functions. Their role during mitosis has made them a target for anti-cancer drugs. However development of resistance has limited their use. It has been established that enhanced beta3-tubulin expression is correlated with reduced response to antimicrotubule agent-based chemotherapy or worse outcome in a variety of tumor settings. However little is known regarding the regulation of beta3-tubulin expression. We investigated the regulatory mechanisms of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…3B). β-estradiol increased the expression of TUBB3 in MCF-7 cells [23]. TUBB3 also was expressed in MDA-MB-231, TMX2-28, and ZR-75 breast cancer cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3B). β-estradiol increased the expression of TUBB3 in MCF-7 cells [23]. TUBB3 also was expressed in MDA-MB-231, TMX2-28, and ZR-75 breast cancer cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila, 3-tubulin expression is enhanced by an exposure to ecdysone, a steroid hormone, through a transcriptional mechanism [80]. Recently, Saussede-Aim J et al found that exposure of ER + MCF-7 cells to estradiol induced 3-tubulin expression in both mRNA and protein levels, while estradiol had no effect on the expression of 3-tubulin in ER -MDA-MB-231 cells [81]. They further showed that co-administration of antiestrogens including tamoxifen or fulvestrant, completely abolished the increase of 3-tubulin mRNA levels due to estradiol in MCF-7 cells, implying that estradiol regulates 3-tubulin expression, and thereby induces resistance of ER + breast tumors to antimicrotubule drugs through an ER -dependent pathway.…”
Section: Enhanced 3-tubulin Expression By E2/ermentioning
confidence: 99%
“…This information further supports androgen regulation and the increased expression of β III-tubulin in castration-resistant tumours. Interestingly, one recent study provided evidence for a potential role of oestradiol and oestrogen receptor (ER) in regulating β III-tubulin in breast cancer cells (Saussede-Aim et al , 2009). Although it remains to be determined as to whether this regulation implies a genomic or a non-genomic effect of ER, this observation could be of interest in PCa as oestrogen-dependent signature has been linked to aggressive characteristics in this tissue (Bonkhoff et al , 2001; Setlur et al , 2008).…”
Section: Discussionmentioning
confidence: 99%